2022
DOI: 10.3390/biomedicines11010077
|View full text |Cite
|
Sign up to set email alerts
|

FT3 to FT4 Conversion Ratio May Be an Independent Prognostic Factor in Pancreatic Cancer Patients

Abstract: Preclinical evidence suggests that T4 can promote tumor growth while T3 can act conversely; therefore, the fT3 and fT4 concentrations should affect overall survival (OS) in cancer patients. The objective of the study was to look for an association between thyroid hormone concentrations in peripheral blood and OS in the pancreatic adenocarcinoma (PDAC) patients group. We included, retrospectively, 15 PDAC patients, without thyroid dysfunction under treatment, who underwent radical surgery, with no prior history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In recent studies, it has been shown that the fT3/fT4 ratio can be an indicator of the prognosis of both cancer and cardiovascular diseases. In this respect, the fT3/fT4 ratio may be a promising parameter for the prognosis of critical diseases [26][27][28][29] . fT3/fT4 ratio may be a prognostic new marker in sepsis, which is among the critical diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, it has been shown that the fT3/fT4 ratio can be an indicator of the prognosis of both cancer and cardiovascular diseases. In this respect, the fT3/fT4 ratio may be a promising parameter for the prognosis of critical diseases [26][27][28][29] . fT3/fT4 ratio may be a prognostic new marker in sepsis, which is among the critical diseases.…”
Section: Discussionmentioning
confidence: 99%